NEW FOSSIL LACEWING LARVAE WITH TRUMPET-SHAPED ELONGATE EMPODIA PROVIDE INSIGHT INTO THE EVOLUTION OF THIS ATTACHMENT STRUCTURE (Rivista italiana di Paleontologia e Stratigrafia, 2024)
The larval life phase often represents the major share of the life span of holometabolans, such as beetles or flies. Therefore, knowledge of these larvae is crucial concerning ecological functions, but also concerning the evolutionary history of the different groups. In the holometabolan group Neuroptera (lacewings), larvae have numerous specialisations, among them the venom-injecting mouthparts, the stylets. Another such very characteristic feature of many lacewing larvae is the empodium, an attachment structure at the tip of the leg, which varies in shape in the larvae of the different lacewing groups. One type of empodium is the elongate trumpet-shaped type, which is found in several lacewing groups today as well as in many fossil representatives, especially well visible due to preservation in amber. Based on the pattern of phylogenetic distribution of the elongate trumpet-shaped empodium, different reconstructions of the evolution of this structure have been put forward, some suggesting possibly convergent evolution, others repetitive losses. In this study, new lacewing larvae preserved in 100-million-year-old amber from Myanmar are presented, which expand the number of lineages with an elongate trumpet-shaped empodium. Based on these new data, the implications on the evolutionary history of the different lineages within Neuroptera are discussed. The fossils demand for an earlier evolution in some reconstructions, but especially for more and later losses of this structure.